The Authenticity Of The Historical Narrative Of The People Of Clothing And Its Impact On Social Life (Journal of the College of Basic Education, 2024)
The Islamic religion emphasized the building of man above all else, as he is the basic nucleus in building societies. The best evidence for this building was the Ahl al-Bayt, peace be upon them, and the most wonderful curricula they developed for raising the individual in a sound and correct manner according to the authentic Muhammad an method. They had a great influence on Society throughout the ages and times, throughout their honorable lives, Al-Manar’s understanding of the Islamic nation in particular and of the global community in general, their understanding of the right path. Therefore, one of the models of human construction among the People of the House, peace be upon them, has been highlighted in these pages by reviewing the authenticity of what came from the narration of the People of the Five Cloaks, peace be upon them, in reliable and authentic historical sources, and then reviewing what was stated in this narration in terms of a sound educational approach that illuminates the way. For a good family life.